Implementation of Learning Indonesian History with Block System at SMK Negeri 3 Salatiga - Harsiwi, Faridha Dwi (Universitas Negeri Semarang, 2019)
This research discusses the implementation of learning Indonesian history with a block schedule system in SMK N 3 Salatiga. This research uses qualitative descriptive, interviews, observation, study documentation, and recording to collect data. The results showed that learning Indonesian history was implemented using Curriculum 2013 and a block schedule system with the application for each block a week. Advocates in implementing learning are moving the class system, compression of 2x2 hours to spending time 40 minutes, compression of history matter, and creativity teachers when giving the lectures. Obstacles in the implementation of learning are the application of a block schedule system, conditions in students themselves, background and commitment of teachers, and the source and media of student learning such as books, Wi-Fi, and LCD limited and marginalization of history subject. The efforts by teachers to overcome the obstacles to build the systematic of learning, follow the theme related to the purpose of education, use basic geography subjects, form the MGMP, use varied media, give strength and grating ahead of the exam, and tasks structured, assigned the students to search the source in the internet and local library.